Giving practitioners a say: Participatory models of research for adult basic education mathematics - Ester D. Leonelli; Martha W. Merson; Bonnie B. Mullinix (Adult Education Research Conference, 1994)
This paper will describe three current, federally funded, and integrally connected projects investigating the teaching of adult basic education mathematics in Massachusetts. Practitioner participation in the research is discussed herewith attention to the pragmatic, professional, and political both in terms of the treatment of practitioners and topics and outcomes of research.